A Literature Review on Islamic Donation - Ririn Riani (SMART Insight, 2021)
Islamic Social Finance is a fast-growing sector. However, because it is still in its infancy, there has been little research done to identify its potential. Infaq is used as an alternative tool to help the Muslim world overcome development problems. Infaq, such as Zakat and Waqf, is one of the most widely used Islamic social finance instruments in the literature. This study found that Islamic donations through infaq play an important role in the experience of suffering of the ummah and society after the Covid-19 pandemic. The data analyzed were more than 49 Scopus indexed research publications. The export data is then processed and analyzed using the R Biblioshiny application program to determine the development map of the infaq theme research. The results showed that the number of publications on the development of the research role had increased. The study also provides several important findings related to the topic of infaq as well as directions for future research development.